TFE3 -rearranged Head and Neck Neoplasms : Twenty-two Cases Spanning the Morphologic Continuum Between Alveolar Soft Part Sarcoma and PEComa and Highlighting Genotypic Diversity - Agaimy, Abbas; Michal, Michael; Abdelsatir, Ali; Abdelsatir, Azza A; Abdulrahim, Sawsan; Laco, Jan; Ihrler, Stephan; Tögel, Lars; Stoehr, Robert; Bishop, Justin A; Din, Nasir Ud; Michal, Michal (The American journal of surgical pathology, 2025)
TFE3 rearrangements characterize histogenetically, topographically, and biologically diverse neoplasms. Besides being a universal defining feature in alveolar soft part sarcoma (ASPS) and clear cell stromal tumor of the lung, TFE3 fusions have been reported in subsets of renal cell carcinoma, perivascular epithelioid cell tumor (PEComa), epithelioid hemangioendothelioma and ossifying fibromyxoid tumors. TFE3 -related neoplasms are rare in the head and neck and may pose diagnostic challenges. We herein describe 22 TFE3 fusion neoplasms affecting 11 males and 11 females aged 4 to 79 years (median, 25) and involving different head and neck sites: sinonasal cavities (n = 8), tongue (n = 4), oral cavity/oropharynx (n = 3), salivary glands (n = 2), orbit (n = 2), and soft tissue or unspecified sites (n = 3). Based on morphology and myomelanocytic immunophenotype, 10 tumors qualified as ASPS, 7 as PEComas (3 melanotic; all sinonasal), and 5 showed intermediate (indeterminate) histology overlapping with ASPS and PEComa. Immunohistochemistry for TFE3 was homogeneously strongly positive in all cases. Targeted RNA sequencing/FISH testing confirmed TFE3 fusions in 14 of 16 successfully tested cases (88%). ASPSCR1 was the most frequent fusion partner in ASPS (4 of 5 cases); one ASPS had a rare VCP::TFE3 fusion. The 6 successfully tested PEComas had known fusion partners as reported in renal cell carcinoma and PEComas ( NONO, PRCC, SFPQ , and PSPC1 ). The indeterminate tumors harbored ASPSCR1::TFE3 (n = 2) and U2AF2::TFE3 (n = 1) fusions, respectively. This large series devoted to TFE3-positive head and neck tumors illustrates the recently proposed morphologic overlap in the spectrum of TFE3 -associated mesenchymal neoplasms. While all PEComas were sinonasal, ASPS was never sinonasal and occurred in diverse head and neck sites with a predilection for the tongue. The indeterminate (PEComa-like) category is molecularly more akin to ASPS but shows different age, sex, and anatomic distribution compared with classic ASPS. We report VCP as a novel fusion partner in ASPS and PSPC1 as a novel TFE3 fusion partner in PEComa (detected in one PEComa). Future studies should shed light on the most appropriate terminological subtyping of these highly overlapping tumors.
Keywords: senioři; Genetic Predisposition to Disease; nádory hlavy a krku; genová přestavba; Perivascular Epithelioid Cell Neoplasms; hybridizace in situ fluorescenční; nádory z perivaskulárních epiteloidních buněk; mladiství; imunohistochemie; Middle Aged; mužské pohlaví; Head and Neck Neoplasms; Adult; mladý dospělý; fenotyp; dítě; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Gene Rearrangement; Sarcoma, Alveolar Soft Part; Child; Biomarkers, Tumor; In Situ Hybridization, Fluorescence; Child, Preschool; Immunohistochemistry; Phenotype; Young Adult; ženské pohlaví; nádorové biomarkery; Humans; předškolní dítě; transkripční faktory BHLH-Zip; lidé středního věku; alveolární sarkom měkkých tkání; dospělí; genetická predispozice k nemoci; Female; Aged; Adolescent; lidé; Male